The Role of Neuronal Pentraxin 2 (NP2) in Regulating Glutamatergic Signaling and Neuropathology - Chapman, Georgina; Shanmugalingam, Ushananthini; Smith, Patrice D. (Frontiers in Cellular Neuroscience, 2020)
Pentraxins are a superfamily of evolutionarily conserved proteins that are characterized by their multimeric architecture and their calcium-dependent binding. They can be broadly grouped into two subfamilies: short pentraxins and long pentraxins. Pentraxins regulate many processes in the brain as well as the periphery. Neuronal pentraxin 2 (NP2/NPTX2), also known as neuronal activity regulated pentraxin (Narp), is an immediate early gene that has been shown to play a critical role in guiding synaptic plasticity. NP2 has been previously linked to excitatory neurotransmission, based on its ability to aggregate excitatory receptors in the central nervous system. The mechanisms mediating the effects of NP2 on excitatory neurotransmission remain unclear and warrants further investigation. This review focuses on the biological features of NP2 and discusses the literature supporting a role for NP2 and other pentraxins in glutamatergic signaling. An analysis of evidence around the role of pentraxins in neuropathology is also reviewed.